Acute infarction in the Artery of Percheron: Case Series - Agrawal, Aditi; Gurung, Pritam; Shrestha, Bishal; Bhatt, Roshan Kumar; Pant, Basant (Annapurna Journal of Health Sciences, 2026)
Artery of Percheron (AOP) infarction is a rare subtype of ischemic stroke resulting from occlusion of a single arterial trunk supplying the bilateral paramedian thalami and rostral midbrain. Because of its variable and often nonspecific clinical presentation, early diagnosis can be challenging. We report two cases of artery of Percheron infarction. The first case involved a 65-year-old woman who presented with headache and altered sensorium for five days. Neurological examination revealed ataxic gait, dysdiadochokinesia, and vertical gaze palsy. Magnetic resonance imaging (MRI) demonstrated acute infarcts in the bilateral thalami and midbrain consistent with AOP infarction. The second case involved an 80-year-old hypertensive man who presented with acute left-sided weakness. Neurological examination revealed mild hemiparesis. MRI brain showed artery of Percheron infarction with hemorrhagic transformation. The patient was managed conservatively and showed good clinical recovery at discharge.Increased awareness of this rare vascular variant can help avoid diagnostic delay and improve patient outcomes.